Does the Monetary Gold Principle Apply to International Courts and Tribunals Generally?. (4th March 2019) - Pomson, Ori
Abstract: In the Monetary Gold case, the International Court of Justice (ICJ) stated that it cannot exercise its jurisdiction over a question when a third state's 'legal interests would … form the very subject-matter of the decision'. The purpose of this article is to answer the question whether this principle applies to international courts and tribunals beyond the ICJ. It begins by providing an overview of jurisprudence concerning the Monetary Gold principle. Following, it analyses the rationales suggested in jurisprudence and legal doctrine for the principle. It is argued that these suggested rationales fail to explain the nature of the principle, or constitute shaky ground for a principle of general applicability. Finally, it is argued that, regardless of the origins of the Monetary Gold principle, it can be grounded on customary international law, and on that basis applies to international courts and tribunals generally.